2017
DOI: 10.1158/1078-0432.ccr-17-0010
|View full text |Cite
|
Sign up to set email alerts
|

MITF-High and MITF-Low Cells and a Novel Subpopulation Expressing Genes of Both Cell States Contribute to Intra- and Intertumoral Heterogeneity of Primary Melanoma

Abstract: Understanding tumor heterogeneity is an important challenge in current cancer research. Transcription and epigenetic profiling of cultured melanoma cells have defined at least two distinct cell phenotypes characterized by distinctive gene expression signatures associated with high or low/absent expression of microphthalmia-associated transcription factor (MITF). Nevertheless, heterogeneity of cell populations and gene expression in primary human tumors is much less well characterized. We performed single-cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 31 publications
6
50
0
Order By: Relevance
“…An even more dedifferentiated phenotype reminiscent of a neural crest stem cell (NCSC) like state is driven by RXRG, devoid of both MITF and AXL, but marked by high levels of SOX10; the population with this phenotype gives rise to minimal residual disease (Rambow et al, 2018) Our data support the observed existence of populations of BRN2 high /MITF low cells and vice versa (Goodall et al, 2008;Thurber et al, 2011). However, our model predicts that any intermediate state can exist and indeed in tumours BRN2 are also found significantly co-expressed with MITF in individual melanoma cells; this can be seen in histology (Thurber et al, 2011) as well as by single-cell gene expression analysis (Ennen et al, 2017). Furthermore, because signals from the tumour microenvironment can influence MAPK signalling the dynamic regulation of MITF downstream of BRAF might explain at least in part the significant heterogeneity in MITF expression that is observed in human tumours.…”
Section: Discussionsupporting
confidence: 81%
“…An even more dedifferentiated phenotype reminiscent of a neural crest stem cell (NCSC) like state is driven by RXRG, devoid of both MITF and AXL, but marked by high levels of SOX10; the population with this phenotype gives rise to minimal residual disease (Rambow et al, 2018) Our data support the observed existence of populations of BRN2 high /MITF low cells and vice versa (Goodall et al, 2008;Thurber et al, 2011). However, our model predicts that any intermediate state can exist and indeed in tumours BRN2 are also found significantly co-expressed with MITF in individual melanoma cells; this can be seen in histology (Thurber et al, 2011) as well as by single-cell gene expression analysis (Ennen et al, 2017). Furthermore, because signals from the tumour microenvironment can influence MAPK signalling the dynamic regulation of MITF downstream of BRAF might explain at least in part the significant heterogeneity in MITF expression that is observed in human tumours.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together this single cell analysis, by and large, confirmed the coexistence of the MITF High and MITF Low phenotypic states, and also revealed that rare drug-resistant cells were found in treatment naïve tumors that would otherwise be classified as MITF High and, therefore, drug-sensitive. However, evidence for any intermediate state, as indicated by the Ennen et al analyses (Ennen et al 2015(Ennen et al , 2017, was not readily apparent. This may be due to the relatively low number of cancer cells analyzed (i.e., only two tumors out of the 20 analyzed exhibited >150 malignant cells) and/or limited number of genes detected per cell due to inherent limitations of the scRNA-seq technique used for this analysis.…”
Section: Phenotypic Heterogeneity Revealed By Single-cell Rna Sequencingmentioning
confidence: 91%
“…Fifth, single-cell gene expression profiling also points toward an intermediate or poised state in which proliferative and invasive gene expression signatures are present. RT-qPCR profiling of single cells from a series of melanoma biopsies revealed the existence of cells simultaneously expressing genes that belong to both the MITF High and MITF Low gene-expression signatures (Ennen et al 2015(Ennen et al , 2017. Although these studies only examined a limited repertoire of genes, they did highlight substantial heterogeneity in gene expression at the single-cell level; something that may have been missed when analyzing mRNA expression levels from bulk tumor samples or from cell lines.…”
Section: The Increasing Diversity Of Melanoma Cell Statesmentioning
confidence: 99%
“…Recently, scattered evidence illustrates the existence of additional, intermediate state(s) (Haass et al 2014;M. Ennen et al 2015;Marie Ennen et al 2017a;Falletta et al 2017;Tsoi et al 2018;Rambow et al 2018;Tuncer et al 2019).…”
Section: Introductionmentioning
confidence: 99%